Youth and politics - Syed Abdullah Idid, Syed Arabi; Moten, Abdul Rashid; Wok, Saodah (Penerbit Universiti Kebangsaan Malaysia, 2011)
Malaysia recognises youth as the agent of change who should be receptive to new ideas, adoptive of technologies and are willing to make changes. To harness the potential of the younger generation, the government has embarked on its ll-point Malaysian Youth Development Action Plan to spearhead youth development until 2020; the year Malaysia aspires to achieve a developed-nation status. The government has also shown determination to recruit the younger generation to participate in the political processes of the country. Members in the Youth Wing of various political parties are being groomed to succeed the current leadership.